Service Level Agreement (SLA) Assurance for Cloud Services: A Survey from a Transactional Risk Perspective - Sun, Le; Singh, Jaipal; Hussain, Omar (ACM, 2012)
Cloud computing is a new paradigm for service-based computing and is gaining popularity. An efficient way for the assurances of the expected service levels in cloud computing is to establish a tailor-made Service Level Agreement (SLA) and to ensure the commitment of SLAs by service providers. In this paper, we conduct a survey of the state of the art in cloud SLA assurance from two aspects – pre- and post-interaction phases, based on which research gaps in existing approaches are identified. Newresearch requirements for SLA assurance are then presented.